Enamel Surface Roughness after Orthodontic Bracket Debonding and Composite Resin Removal by Two Types of Burs - Shafiee, Hassan-Ali; Mohebi, Shadi; Ameli, Nazilla; Omidvar, Ramin; Akbarzadeh, Alireza (Journal of Dental School, 2019)
Objective: Increased enamel surface roughness following orthodontic bracket debonding leads to increased plaque accumulation and enamel decalcification. Therefore, different methods are employed to achieve smoother enamel surfaces after bracket debonding. This study compared enamel surface roughness following orthodontic bracket debonding and composite resin removal using white stone and tungsten carbide burs. Methods: In this in-vitro, experimental study, 20 first and second premolars of 10-20 year-olds were collected and their crowns were mounted in acrylic blocks. Roughness of the buccal surfaces of teeth was determined by atomic force microscopy (AFM) and the brackets were bonded to the teeth. After bracket debonding, composite remnants were removed using white stone and tungsten carbide burs. Parameters of enamel surface roughness were determined by AFM and time required for composite removal was also calculated. Repeated measures ANOVA was used to assess the changes in parameters based on the time of measurement, type of bur and their interaction effect. Time required for composite resin removal by bur was analyzed using one-way ANOVA and Tukey’s multiple comparisons. Results: Resin removal increased enamel surface roughness compared to the baseline values in all groups. However, no significant differences were noted between the two types of burs regarding arithmetic average of the roughness profile (Ra), the root mean square roughness (Rq) and the maximum peak-to-valley height in the sampling length (Rt) after resin removal. Time required for resin removal with tungsten carbide bur (34.2 seconds) was significantly shorter than with white stone bur (56.6 seconds)(both ps<0.0001). Conclusion: Considering the similar enamel surface roughness values achieved by the two burs, tungsten carbide burs are recommended for resin removal following orthodontic bracket debonding.